Architectures de la petite industrie urbaine : l’exemple des Lilas (Seine-Saint-Denis) - Nicolas Pierrot (In Situ)
The factories and artisans’ workshops surveyed in the suburban town of Les Lilas were built essentially during the XXth century. Unlike the town of La Plaine-Saint-Denis, whose heavy industry - namely chemical and metallurgical - generated a large unskilled workforce, Les Lilas attracted, from the second half of the XIXth century onward, numerous and varied industries that hired skilled workers. These companies were disseminated throughout the town in discreet workshops : ornate factories are not a "Lilasian" tradition. A morphological and architectural study allows us to follow the evolution of the workshops and factories found in back courtyards, along alleys or sometimes more visibly located, and to understand the different ways they wove themselves into the urban fabric of Les Lilas.